2017
DOI: 10.4025/actascianimsci.v39i3.34807
|View full text |Cite
|
Sign up to set email alerts
|

<b>Milk composition and blood metabolic profile from holstein cows at different calving orders and lactation stages

Abstract: ABSTRACT. This study aimed to evaluate milk composition and metabolic profile of Holstein cows at different calving orders in the beginning, middle, and end of lactation. One hundred ten Holstein cows were housed in a free stall system receiving the same diet and were grouped according to calving order (first, second, third, and fourth calving) and days in milk (DIM): early (1-90 DIM), middle (91-180 DIM), and end of lactation (over 181 DIM) for comparing milk yield, milk composition, and blood metabolic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…It is observed that the BHCF diet was more productive in fat, protein, lactose, non-fat solids and total solids (21.87, 26.30, 25.29 and 20.85%) relative to the SS diet, respectively. Milk production and its chemical composition may suffer interference from the diet offered to the animal, as it is responsible for supplying most of the precursors for milk synthesis and its constituents (Dias et al, 2017;Talpur, Bhanger, & Memon, 2009). The behavior of these data for higher milk production followed the DMI and CPI (kg day -1 ) for the diets, so that the highest production was observed for the BHCP diet when compared to the SS (Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the BHCF diet was more productive in fat, protein, lactose, non-fat solids and total solids (21.87, 26.30, 25.29 and 20.85%) relative to the SS diet, respectively. Milk production and its chemical composition may suffer interference from the diet offered to the animal, as it is responsible for supplying most of the precursors for milk synthesis and its constituents (Dias et al, 2017;Talpur, Bhanger, & Memon, 2009). The behavior of these data for higher milk production followed the DMI and CPI (kg day -1 ) for the diets, so that the highest production was observed for the BHCP diet when compared to the SS (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Higher food intake results in increased intake of nutrients for the animal, resulting in better milk production. In addition, dietary protein is degraded and made available in the bloodstream in the form of amino acids and peptides and can be used in the synthesis of milk proteins or even in the synthesis of glucose (neoglygenesis), thus increasing production (Dias et al, 2017;Talpur et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Desta forma, a avaliação internacional da qualidade do leite é realizada pela contagem de células somáticas (CCS), contagem bacteriana total (CBT) e contaminantes (Santos & Fonseca, 2019), sendo que, os mesmos em desacordo com a Instrução Normativa vigente prejudicam o rendimento industrial dos produtos lácteos, tempo de prateleira, segurança alimentar dos produtos (Lampugnani et al, 2018), além da saúde da glândula mamária (Neves et al, 2019). Development, v. 9, n. 11, e1419119490, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9490 As transformações que ocorrem na qualidade, composição e produção do leite são ligadas a diversos fatores, como estágio de lactação e o número de lactação (Dias et al, 2017), sanidade dos animais, manejo higiênico durante a ordenha (Botton et al, 2019), higienização do ordenhador (Dias et al, 2015), fatores nutricionais (Werncke et al, 2016) e das alterações climáticas contribuintes para o estresse térmico ao rebanho e interferindo no metabolismo animal (Ludovico et al, 2015).…”
Section: Introductionunclassified
“…Sendo assim, a composição do leite permite monitorar o rebanho leiteiro a partir da gordura, proteína, lactose, extrato seco total (EST), extrato seco desengordurado (ESD), contagem de células somáticas (CCS) e contagem padrão em placas (CPP), permitindo assim, analisar as falhas na nutrição, no manejo e correção dos mesmos pelo produtor (DIAS et al, 2017). Além disso, a CCS e CPP são considerados bons indicadores internacionais para avaliar a qualidade do leite (PEIXOTO et al, 2016), rendimento industrial e determinação da segurança alimentar do produto (LAMPUGNANI et al, 2018).…”
Section: Introductionunclassified